1993
DOI: 10.1152/ajpcell.1993.264.1.c93
|View full text |Cite
|
Sign up to set email alerts
|

Immunofluorescent localization of the ubiquitin-activating enzyme, E1, to the nucleus and cytoskeleton

Abstract: Ubiquitin, a 76-amino acid protein, is covalently attached to abnormal and short-lived proteins, thus marking them for ATP-dependent proteolysis in eukaryotic cells. Ubiquitin is found within the cytoplasm, nucleus, microvilli, autophagic vacuoles, and lysosomes. The ubiquitin-activating enzyme, E1, catalyzes the first step in ubiquitin conjugation. To date, very little is known about the subcellular distribution of this enzyme. We have utilized immunofluorescence and immunoblotting to examine the cellular dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 1 publication
1
17
0
Order By: Relevance
“…This activation is accompanied by concomitant IB␣ proteolysis. Of note, ubiquitin and ubiquitin-activating enzymes are also localized to microtubules (49,67). During the preparation of this article, Régnier et al identified conserved helix-loop-helix ubiquitous kinase (CHUK) as an IB kinase capable of phosphorylating Ser-32 and Ser-36, modifications that are required for targeted degradation of IB␣ via the ubiquitin-proteasome pathway (54).…”
Section: Discussionmentioning
confidence: 99%
“…This activation is accompanied by concomitant IB␣ proteolysis. Of note, ubiquitin and ubiquitin-activating enzymes are also localized to microtubules (49,67). During the preparation of this article, Régnier et al identified conserved helix-loop-helix ubiquitous kinase (CHUK) as an IB kinase capable of phosphorylating Ser-32 and Ser-36, modifications that are required for targeted degradation of IB␣ via the ubiquitin-proteasome pathway (54).…”
Section: Discussionmentioning
confidence: 99%
“…Cell Culture and Transfection-HeLa cells were cultured in Dulbecco's modified Eagle's medium and 10% fetal calf serum and maintained at 37°C and 5% CO 2 in a humidified chamber as described previously (9). Transient transfections were performed using a calcium phosphate coprecipitation method as described by Chen and Okayama (14); cells were processed 40 -48 h following transfection.…”
Section: Methodsmentioning
confidence: 99%
“…Because Ub requires activation prior to participation in any subsequent reactions, E1 plays a key role in the Ub-conjugating pathway. E1 is localized in both the nucleus and the cytoplasm (8,9) and exists as two isoforms E1a (117 kDa) and E1b (110 kDa) (10,11). To investigate the nature of these isoforms, epitope-tagged cDNA constructs of E1 were generated where the hemagglutinin (HA) epitope tag was placed after the first methionine (amino acid 1; HA1-E1) or after the second methionine (amino acid 40; HA2-E1) (11).…”
mentioning
confidence: 99%
“…El proteins and their encoding genes have been isolated from rabbit, yeast, wheat, human, and mice. Initially, UBE1 localizes in both the nucleus and the cytoplasm and exists as two isoforms E1a (117 kDa) and E1b (110 kDa) in mammals [Handley et al, 1991;Schwartz et al, 1992;Trausch et al, 1993;Stephen et al, 1997]. In recent studies, at least four kinds of E1 (UBE1, AOS1/UBA2, APP-BP1/UBA3, and APG12) exist, each of which has different function in organism.…”
mentioning
confidence: 99%